Hubungan Antara Kecerdasan Adversitas dengan Kemalasan Sosial pada Siswa SMA MTA Surakarta - Zukhrifa Izzatur Rafi'ah; Afia Fitriani (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
Group studies or group assignments are commonly implemented in schools. However, they are susceptible to social loafing, a condition in which individuals exert less effort when working in group settings than when working alone. One factor that may influence social loafing is adversity quotient, defined as the individual’s ability to respond effectively to challenges or difficulties. This research explores the correlation between the adversity quotient and social loafing among SMA MTA Surakarta students. The research employed a quantitative correlational method with a sample of 241 students selected through proportionate stratified random sampling. Data were collected using scales for adversity quotient (r=0.895) and social loafing (r=0.814). The study found a significant negative correlation (r=-0.205, p<0,05) between these two variables. Thus, this confirms the hypothesis of a strong, negative correlation between adversity quotient and social loafing among SMA MTA Surakarta students.